The Study Of Law In The Theory Of Leadership John E. Maxwell As Well As Its Application Against The Leadership Of The Effective - Ranto Ranto (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2021)
In the Legal Foundation That Vamp this, the cornerstone of which is the basis for true leadership it is the belief, not the belief in the sense of faith or religion, but rather a statement of the credibility of someone that can be trusted, or childbirth trust of those they lead. So trust is the cornerstone of leadership. The Law Of True Leadership: Apply The Law Of-This Law Then People Will Become Your Followers. While the confidence in his own awakened/formed mainly from the role of the character and integrity to be a key factor for the creation of trust in leadership. That character is the basis of the defense is at the root of the realization of beliefs that sustain and maintain its leadership of the collapse. While trust is the cornerstone of strong leadership.